2009
DOI: 10.1093/brain/awp156
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Discrimination Threshold: VBM evidence for an endophenotype in adult onset primary torsion dystonia

Abstract: Familial adult-onset primary torsion dystonia is an autosomal dominant disorder with markedly reduced penetrance. Most adult-onset primary torsion dystonia patients are sporadic cases. Disordered sensory processing is found in adult-onset primary torsion dystonia patients; if also present in their unaffected relatives this abnormality may indicate non-manifesting gene carriage. Temporal discrimination thresholds (TDTs) are abnormal in adult-onset primary torsion dystonia, but their utility as a possible endoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 37 publications
(49 reference statements)
11
144
2
4
Order By: Relevance
“…(Bradley et al, 2009;Scontrini et al, 2009;Tinazzi et al, 2004;Kimmich et al, 2014;Kagi et al, 2013) 5 out of 14 (36%) non-affected 1 st degree relatives had abnormal visuotactile temporal discrimination thresholds. Considering that only 50% of 1 st degree relatives are expected to be gene mutation carriers, the finding supports previous reports that subtle sensory abnormalities represent a trait or endophenotype of gene mutation carriage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(Bradley et al, 2009;Scontrini et al, 2009;Tinazzi et al, 2004;Kimmich et al, 2014;Kagi et al, 2013) 5 out of 14 (36%) non-affected 1 st degree relatives had abnormal visuotactile temporal discrimination thresholds. Considering that only 50% of 1 st degree relatives are expected to be gene mutation carriers, the finding supports previous reports that subtle sensory abnormalities represent a trait or endophenotype of gene mutation carriage.…”
Section: Discussionmentioning
confidence: 98%
“…The fact that the latter research group found the largest differences in the visual and tactile compared to mixed (visuo-tactile) paradigm is intriguing and hard to explain. (Bradley et al, 2009;Kimmich et al, 2014) (Tinazzi et al, 2002)patients with IAOCD multimodal (visuo-tactile) temporal discrimination might be more affected compared to the unimodal temporal discrimination; i) the parietal lobe as an important center of multimodal sensory integration is part of the dystonia network (Lacruz et al, 1991;Leon and Shadlen, 2003;Neychev et al, 2011;Pastor et al, 2004), ii) this notion receives support by the finding that patients with a good effect to a sensory trick perform significantly better in the visuo-tactile sensory discrimination and that the parietal lobe is activated while performing an effective sensory trick (Kagi et al, 2013;Naumann et al, 2000), iii) the superior colliculi, where multisensory (visual, tactile, auditory) inputs converge are involved in head-turn generation with its cephalomotor premotor neurons (Hutchinson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Studies of sensory processing in dystonia patients using spatial discrimination thresholds (SDT) or temporal discrimination thresholds (TDT) (tests of discrimination between two close-interval sensory stimuli) have found abnormal SDTs and TDTs in patients with adult-onset sporadic primary dystonia and in their unaffected relatives. 40,41 Notably, a recent study comparing SDT and TDT as potential endophenotypes found that TDT was a much more reliable measurement. 42 'Double pulse' repetitive transmagnetic stimulation (rTMS) studies have demonstrated evidence of decreased cortical inhibition and increased excitability in various forms of dystonia, including in both DYT1 dystonia patients and DYT1 non-manifesting carriers, 43 and in the hand motor cortex in both focal hand dystonia patients as well as in patients with blephorospasm.…”
Section: Myoclonus Dystoniamentioning
confidence: 99%
“…38,39 Studies of sensory processing in dystonia patients using spatial discrimination thresholds (SDT) or temporal discrimination thresholds (TDT) (tests of discrimination between two close-interval sensory stimuli) have found abnormal SDTs and TDTs in patients with adult-onset sporadic primary dystonia and in their unaffected relatives. 40,41 Notably, a recent study comparing SDT and TDT as potential endophenotypes found that TDT was a much more reliable measurement. 42 'Double pulse' repetitive transmagnetic stimulation (rTMS) studies have demonstrated evidence of decreased cortical inhibition and increased excitability in various forms of dystonia, including in both DYT1 dystonia patients and DYT1 non-manifesting carriers, 43 and in the hand motor cortex in both focal hand dystonia patients as well as in patients with blephorospasm.…”
Section: Myoclonus Dystoniamentioning
confidence: 99%